Все страны мира: энцикл. справ. / сост.: И. О. Родин, Т. М. Пименова - Родин И. О. (Вече, 2001)
Экземпляры: ДО ст.аб. (20160415) / Инвентарный номер: 52921 / Цена: 140.00. / Сис.шифр: 26.8я2 / Авт.знак: В 84 / ГРНТИ: 39.23 / ББК: 26.8я2